A constraint-based approach for identifying the urban–rural fringe of polycentric cities using multi-sourced data. Issue 1 (2nd January 2022) - Yang, Jing; Dong, Jingwen; Sun, Yizhong; Zhu, Jie; Huang, Yi; Yang, Sheng
ABSTRACT: Studies on urban–rural fringes, which represent regions facing various urbanization problems caused by rapid expansion, have steadily increased in recent years. However, problems persist in the quantitative delimitation of such regions. Based on the characteristics of abrupt urbanization-level changes in urban–rural fringe areas, we propose a constraint-based method in this study to detect the urban–rural fringes of cities with a spatial polycentric structure of 'Main center–Subcenter' based on data from multiple sources. We used the proposed approach to delimitate the fringe areas of Jiangyin and Zhangjiagang and identify their urban main center and subcenter pre-defined by their city master plans, towns, and rural hinterlands. Comparison of the identified results of different single urbanization indices, a single detection center, kernel density estimation, and a single constraint revealed that the patch density and Shannon's diversity index of the proposed method were higher in urban–rural fringes and smaller in city centers and rural hinterlands. This suggests that the landscape of urban–rural fringes delimitated by the proposed method is more fragmented, diverse, and complicated, thereby performing better. This study is significant for future urban spatial analysis, planning, and management.